Dining Patterns And Physical Activities With Obesity Events In Household Mothers In Taccorong Village, Gantarang District - Nurazisah; A.Nurlaela Amin; Muriyati (Lembaga Penelitian dan Pengabdian Masyarakat Stikes Panrita Husada Bulukumba, 2019)
Based on the preliminary survey researchers the number of obesity increased from March and April to May and June 2018. From the results of research conducted by researchers, more eating patterns are less good than good diet and more who do less physical activity than moderate and heavy physical activity. This study aims to determine the relationship between diet and physical activity with the incidence of obesity in housewives in the Taccorong Village, Gantarang District. This study uses an analytical design with a cross-sectional approach. Sampling was done by purposive sampling technique. The population in this study were 1011 people. The sample in this study were 47 respondents. Data analysis using the Chi-square test on diet and using the Kolmogorov Smirnov test on physical activity. The results of the analysis of diet with obesity using the chi-square test obtained the value (p = 0.000) indicating that there was a significant relationship between diet and the incidence of obesity in housewives in Taccorong Village. Whereas physical activity analysis with obesity using Kolmogorov Smirnov test obtained values ​​(p = 0.022) showed that there was a relationship of physical activity with the incidence of obesity in housewives in the Taccorong Village. The conclusion of this study is that there is a relationship between diet and physical activity with the incidence of obesity in housewives in the Taccorong Village, Gantarang Subdistrict, Bulukumba District. It is recommended for housewives to behave in a healthy life by maintaining a good diet and regulating physical activity well in order to avoid various degenerative diseases due to complications from obesity. For Bontonyeleng health centers to be able to form cadres to detect total obesity. For the next researcher who uses food recall 24 hours if using repeated time.